Synthesis and antimicrobial activity of some new macrocyclic bis-sulfonamide and disulfides - Eshghi, Hossein; Rahimizadeh, Mohammad; Zokaei, Mahmood; Eshghi, Shaghayegh; Eshghi, Shohreh; Faghihi, Zinab; Tabasi, Elaheh; Kihanyan, Mehdi (European Journal of Chemistry, 2011)
Synthesis and antimicrobial evaluation of some typical macrocyclic crown ethers including amide, sulfonamide, and disulfide moieties are reported. Novel macrocyclic bis-sulfonamide, amide, and disulfides are prepared by reacting the bis-chlorides and diamines by fast addition method. The antimicrobial activities of the synthesized compounds are measured. Bis-sulfonamide and disulfide crown ethers showed antibacterial activities against most strains tested.